A genetic screen for regulators of muscle morphogenesis in Drosophila. Issue 8 (16th May 2021) - Ou, Tiffany; Huang, Gary; Wilson, Beth; Gontarz, Paul; Skeath, James B; Johnson, Aaron N
Abstract: The mechanisms that determine the final topology of skeletal muscles remain largely unknown. We have been developing Drosophila body wall musculature as a model to identify and characterize the pathways that control muscle size, shape, and orientation during embryogenesis. Our working model argues muscle morphogenesis is regulated by (1) extracellular guidance cues that direct muscle cells toward muscle attachment sites, and (2) contact-dependent interactions between muscles and tendon cells. While we have identified several pathways that regulate muscle morphogenesis, our understanding is far from complete. Here, we report the results of a recent EMS-based forward genetic screen that identified a myriad of loci not previously associated with muscle morphogenesis. We recovered new alleles of known muscle morphogenesis genes, including back seat driver, kon-tiki, thisbe, and tumbleweed, arguing our screen had the depth and precision to uncover myogenic genes. We also identified new alleles of spalt-major, barren, and patched that presumably disrupt independent muscle morphogenesis pathways. Equally as important, our screen shows that at least 11 morphogenetic loci remain to be mapped and characterized. Our screen has developed exciting new tools to study muscle morphogenesis, which may provide future insights into the mechanisms that regulate skeletal muscle topology.